SREBF1/MicroRNA-33b Axis Exhibits Potent Effect on Unstable Atherosclerotic Plaque Formation In Vivo. Issue 10 (October 2018) - Nishino, Tomohiro; Horie, Takahiro; Baba, Osamu; Sowa, Naoya; Hanada, Ritsuko; Kuwabara, Yasuhide; Nakao, Tetsushi; Nishiga, Masataka; Nishi, Hitoo; Nakashima, Yasuhiro; Nakazeki, Fumiko; Ide, Yuya; et al.
Abstract : Objective—: Atherosclerosis is a common disease caused by a variety of metabolic and inflammatory disturbances. MicroRNA (miR)-33a within SREBF2 (sterol regulatory element-binding factor 2) is a potent target for treatment of atherosclerosis through regulating both aspects; however, the involvement of miR-33b within SREBF1 remains largely unknown. Although their host genes difference could lead to functional divergence of miR-33a/b, we cannot dissect the roles of miR-33a/b in vivo because of lack of miR-33b sequences in mice, unlike human. Approach and Results—: Here, we analyzed the development of atherosclerosis using miR-33b knock-in humanized mice under apolipoprotein E–deficient background. MiR-33b is prominent both in human and mice on atheroprone condition. MiR-33b reduced serum high-density lipoprotein cholesterol levels and systemic reverse cholesterol transport. MiR-33b knock-in macrophages showed less cholesterol efflux capacity and higher inflammatory state via regulating lipid rafts. Thus, miR-33b promotes vulnerable atherosclerotic plaque formation. Furthermore, bone marrow transplantation experiments strengthen proatherogenic roles of macrophage miR-33b. Conclusions—: Our data demonstrated critical roles of SREBF1 -miR-33b axis on both lipid profiles and macrophage phenotype remodeling and indicate that miR-33b is a promising target for treating atherosclerosis. Abstract : Supplemental Digital Content is available in the text.